MODEL PERENCANAAN PROGRAM AKSI DESA MANDIRI PANGAN DI DESA KEBON GUNUNG, PURWOREJO - Harsanti, Febtory Setyo; Murdiyanto, Eko; Senjawati, Nanik Dara (Jurnal Dinamika Sosial Ekonomi, 2018)
Food self-sufficient Village Program is an action program to reduce food insecurity and nutrition through the utilization of resources, institutions and local rural wisdom. Ths research was conducted because of the difference of success among the beneficiary villages, despite having the same top down program. The objectives of this study are 1) To examine the cause of unsuccessful for Food Self-sufficient Village Action Program in Kebon Gunung Village; 2) Formulate the appropriate program planning approach for the people of Kebon Gunung Village. This research method is qualitative with sipported quantitative data. Determining the location and selection of respondents using purposive method. Analysis method using Miles and Huberman model through three stages, namely 1) reduction of data; 2) Presentation of data; 3) Verify. The results of the research indicate that 1) Food Self-sufficient Village Action Program has not been successful due to a) Limited budget, so that the organizers can not carry out continuous assistance and haver never conducted training for beneficiaries; b) There is no coordination between the facilitator with village apparatus in determining Poor Households, so that the beneficiaries are selected not based on criteria but directly elected by the Village Head; c) The facilitator locks the socialization of the Village Food Team task, so it has not worked and there is no village food barn yet; d) The facilitator has not provided any socialization regarding the establishment of the Village Finance Institution, so it has not been established; e) The facilitator has not been actively engaged in integration with the relevant agencies (stakeholders); f) Beneficiaries less, so there has not been productive efforts. 2) Approach Planning of the right program is top down with the assistance because the people of Kebon Gunung village (beneficiaries) is a transitional society.Â Keywords: Planning Model, Food Self-sufficient Village Action Program